1990
DOI: 10.1175/1520-0477(1990)071<0002:sombto>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Microwave Brightness Temperatures of an Evolving Hailstorm at SSM/I Frequencies

Abstract: A simulation of the appearance of an intense hailstorm in the passive microwave spectrum is conducted in order to characterize the vertical sources of radiation that contribute to the top-of-atmosphere microwave brightness temperatures (Te) which can be measured by satellite-borne radiometers. The study focuses on four frequencies corresponding to those used on the USAF Special Sensor Microwave Imager (SSM/I), a recently launched payload flown on the U.S. Air Force DMSP satellites. Computation of the microwave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Both infrared (IR) and microwave (MW) emissions are used for precipitation retrievals. While IR estimates of rainfall are only indirect because IR measurements are sensitive only to the uppermost layers of clouds, MW observations have the great advantage of providing a more direct measurement of the precipitation due to the ability of MW radiation to penetrate precipitating clouds and interact with its liquid and ice hydrometeors (e.g., Mugnai et al, 1990;Wilheit et al, 1994;Weng and Grody, 2000;Bennartz and Petty, 2001;Bauer et al, 2005). Passive microwave (PMW) techniques for the estimation of precipitation have seen great advances over the past years, due largely to the increased number of radiometers available, with improved sensing capabilities (i.e., higher spatial resolution, number of available channels useful for precipitation retrieval) and due to the several theoretical studies on microwave radiative transfer modeling through precipitating clouds (e.g., Mugnai et al, 1993;Wilheit et al, 1994;Smith et al, 1998Smith et al, , 2002Stephens and Kummerow, 2007;Skofronick-Jackson and Johnson, 2011).…”
Section: P Sanò Et Al: the Passive Microwave Neural Network Precipimentioning
confidence: 99%
“…Both infrared (IR) and microwave (MW) emissions are used for precipitation retrievals. While IR estimates of rainfall are only indirect because IR measurements are sensitive only to the uppermost layers of clouds, MW observations have the great advantage of providing a more direct measurement of the precipitation due to the ability of MW radiation to penetrate precipitating clouds and interact with its liquid and ice hydrometeors (e.g., Mugnai et al, 1990;Wilheit et al, 1994;Weng and Grody, 2000;Bennartz and Petty, 2001;Bauer et al, 2005). Passive microwave (PMW) techniques for the estimation of precipitation have seen great advances over the past years, due largely to the increased number of radiometers available, with improved sensing capabilities (i.e., higher spatial resolution, number of available channels useful for precipitation retrieval) and due to the several theoretical studies on microwave radiative transfer modeling through precipitating clouds (e.g., Mugnai et al, 1993;Wilheit et al, 1994;Smith et al, 1998Smith et al, , 2002Stephens and Kummerow, 2007;Skofronick-Jackson and Johnson, 2011).…”
Section: P Sanò Et Al: the Passive Microwave Neural Network Precipimentioning
confidence: 99%
“…Using the numerical-model simulation, Mugnai et al [58] investigated vertical sources of radiation that contribute to the top-of-atmosphere Tbs in terms of the four frequencies corresponding to the SSM/I. They demonstrated that the 85-GHz signals were emissions from the upper level liquid and ice scattering in the upper reaches of tall precipitation clouds.…”
Section: B Scattering Algorithm Using 85 and 37 Ghzmentioning
confidence: 99%
“…In any given storm, these values may not be coincident. However, based on theory (Wilheit et al 1982;Mugnai et al 1990;Adler et al 1991;Vivekanandan et al 1991) and observations (Spencer 1986;Hakkarinen and Adler 1988;Rutledge and MacGorman 1988;Fulton 1988, 1994;Fulton and Heymsfield 1991;Keighton et al 1991;Toracinta et al 1996;Mohr et al 1996;Petersen et al 1996Petersen et al , 1999Carey and Rutledge 2000), including detailed examination of hundreds of individual precipitation features from this dataset, we are making an implicit assumption that the relationships between them are sufficiently robust for describing and comparing the relative strengths of the strongest convective events within convective systems and the relationship to lightning. Table 1 shows that precipitation features occur with greater frequency in the tropical ocean regions than in the tropical land regions even when normalized by the respective region areas.…”
Section: B Precipitation Feature Database and Study Domainmentioning
confidence: 99%